2021
DOI: 10.1177/15562646211043985
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ Preferences and Reasons for Wanting Feedback of Individual Genetic Research Results From an HIV-TB Genomic Study: A Case Study From Botswana

Abstract: The feedback of individual results of genomics research is an ethical issue. However, which genetic results African participants would like to receive and why, remains unclear. A qualitative study was conducted to collect data from 44 adolescents and 49 parents/caregivers of adolescents enrolled in a genomic study in Botswana. Almost all the participants wanted to receive genetic results. Parents and caregivers wanted to receive results across all categories of genetic conditions discussed in the study, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Second, survey and interview participants leveraged trust in science to manage the (clinically) uncertain nature of genomic information. Many participants implied that trust in future developments in genomic medicine motivated them to participate in genome sequencing, even if current findings are limited [ 88 , 89 ]. Again, attitudes towards science in IAM participants in particular might be shaped by their familiarity with the research context.…”
Section: Discussionmentioning
confidence: 99%
“…Second, survey and interview participants leveraged trust in science to manage the (clinically) uncertain nature of genomic information. Many participants implied that trust in future developments in genomic medicine motivated them to participate in genome sequencing, even if current findings are limited [ 88 , 89 ]. Again, attitudes towards science in IAM participants in particular might be shaped by their familiarity with the research context.…”
Section: Discussionmentioning
confidence: 99%
“…While both consortia are led and funded by institutions from HICs, what is significant for the topic at hand is that both formed dedicated ethics working groups, comprising bioethicists from across the African continent. These groups have focused on ethical and regulatory issues arising from the studies they are attached to, using ethical frameworks that are sensitive to the socio-cultural context, as well as conducting related empirical ethics research to ascertain the attitudes and beliefs of different populations about genetic information, particular explanatory models of disease, the stigmatising of certain disorders, and views about feedback of study findings, among others (De Vries, Landouré & Wonkam, 2020;Matimba et al, 2022;Ralefala et al, 2021). Along with the ethics and regulatory working group, H3Africa includes working groups focused on outreach and communication as well as ethics and community engagement (Tindana et al, 2015).…”
Section: Building Neuroethics Capacity Through the Growth Of Neurosci...mentioning
confidence: 99%
“…Research participants consider receiving their genomics and genetics results from researchers as a way of showing respect and value for their contribution to the research project's success (Ralefala, Kasule et al, 2020). Studies have reported that participants desire to receive individual results across all categories of genetic medical conditions ranging from severe, non-preventable, and non-treatable as well as personal utility (Matshabane et al, 2022; Ralefala et al, 2021). A qualitative study conducted among parents and caregivers of children and adolescents involved in an HIV-TB genomic study in Botswana reported that almost all participants wanted to receive their genetic results (Ralefala et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that participants desire to receive individual results across all categories of genetic medical conditions ranging from severe, non-preventable, and non-treatable as well as personal utility (Matshabane et al, 2022; Ralefala et al, 2021). A qualitative study conducted among parents and caregivers of children and adolescents involved in an HIV-TB genomic study in Botswana reported that almost all participants wanted to receive their genetic results (Ralefala et al, 2021). However, satisfying the research participants’ demand for genomics and genetics analyses remains a debate among researchers and bioethicist communities on the African continent (Kasule et al, 2022; Kisiangani et al, 2022; Mwaka et al, 2021b; Ochieng et al, 2021b; Ralefala, Kasule et al, 2022).…”
Section: Introductionmentioning
confidence: 99%